Novel Insights Into Basic Research: Exploring Molecular Effects Of Trans-Cinnamaldehyde And Eugenol On α7 And Muscle Acetylcholine Receptors Via Electrophysiological Assessment - Hernando, Guillermina Silvana (2023)
Naturally occurring bioactive compound have been used in tradi- tional medicine for the treatment of various diseases for many cen- turies. In modern times, there has been a renewed interest in nat- ural compounds and essential oils for their medicinal properties. In recent years, it has been demonstrated that many of these natural compounds act on neurotransmitter receptors, including Cys-loop receptors such as the nicotinic acetylcholine receptor (nAChR). nA- ChRs form a family of ACh-gated ion channels found in the central and peripheral nervous systems, involved in processes like muscle contraction, memory, and attention. In this project, we assessed the molecular-level effects of trans-cinnamaldehyde (TC) and eugenol (EGN) -the two naturally occurring phenylpropanoids present in Cinnamomum oil- on two types of mammalians nAChR, which are involved in several pathological disorders. As TC and EGN are mul- titarget drug, there is a need to establish the molecular mechanisms by which they may exert therapeutic as well as adverse effects. Through single-channel recordings, we observed that TC exerts a negative modulatory effect on both α7 and muscular nAChR. On the one hand, TC leads to a marked reduction of α7 activity by decreas- ing the frequency of activation episodes without causing changes in amplitude and in the open durations. On the other hand, recordings from muscular nAChR exhibit a concentration-dependent reduction in open channel duration within the micromolar range, induced by both TC and EGN. This change is accompanied by a shift towards shorter durations in the main closed component. The modulation of nAChRs is of pharmacological relevance and should be considered in the evaluation of the potential therapeutic uses of TC and EGN as. Our findings offer insights into how natural compounds influence Cys-loop receptors, which remain unexplored and are important tar- gets in various therapeutic approaches